Physiological and transcriptomic analyses reveal the mechanism of improved mango storage by pre-harvest GA₃ and CPPU treatment - Tang-xin Jiang; Bi-xia Wang; Zhi-xi He; Jing-tang Zhang; Cong Luo; Xin-hua He (Postharvest Biology and Technology, 2027)

High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Oxidized Late Devonian arc intrusion in the Jiangda area, eastern Tibet: Implication for heterogeneous porphyry Cu-Au fertility of Paleo-Tethyan arc magmas - Rui Ma; Ming-Liang Huang; Lei-Luo Xu; Jing-Jing Zhu; Bao-Di Wang; Hong-Rui Zhang; Rui-Zhong Hu; Xing-Chun Zhang; Xian-Wu Bi (Journal of Asian Earth Sciences, 2026)

Multiscale modeling for separating methylnaphthalene from light cycle oil via benzyl alcohol-based deep eutectic solvent - Zhen Xu; Yajing Luo; Yuxuan Zhang; Rongshan Bi; Wenxuan Zhao; Pan Xu; Guoxuan Li (Chemical Engineering Journal, 2026)

An eco-friendly integrated short-process of ffor low-grade nickel laterite ore utilization: Glycolic acid leaching kinetics and direct hydro-thermal synthesis of spinel NiFe2O4 anodes - Anlu Wei; Wenning Mu; Xiaolong Bi; Xiang Li; Xuefei Lei; Shaohua Luo (Process Safety and Environmental Protection, 2026)

Layer‑resolved core-shell hydrogel for in situ fluorescence monitoring of Hg(II) adsorption and removal - Xiaoya Bi; Lijun Luo; Xin Gao; Zixiang Liao; Yue Ren; Cheng Xu; Libo Li; Tianyan You (Journal of Hazardous Materials, 2026)

Boosting uranium adsorption performance by engineering flexible linkers in tannin-immobilized polyamide membranes - Hongru Zhang; Linping Yan; Zihe Li; Wei Luo; Xuepin Liao; Bi Shi (Desalination, 2026)

Azo-sulfonate functionalized collagen fibers for rapid and high-capacity uranium capture - Zihe Li; Linping Yan; Wei Luo; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2026)

Culture-enriched sequencing reveals river confluence sediments as high-risk reservoirs of viable multidrug-resistant pathogens - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Zhiwei Zhu (Journal of Hazardous Materials, 2026)

Cold plasma technology for the modification and quality control of food components via exogenous RONS: Mechanisms, strategies, and future prospects - Xiaotong Fan; Jiabao Ni; Yanxiang Bi; Shiye Luo; Pingping Dong; Shenyuan Quan; Jiaxin He; Xiaoming Fang (Food Bioscience, 2026)

Intensity-resolved classification of forest fire smoke via fused satellite and ground-based optical climatology - Yangyang Ma; Jie Luo; Kaitao Li; Yongqiang Zhang; Hengze Zhao; Pei Li; Meihua Bi; Xuefang Zhou (Environmental Research, 2026)

Rhizosphere fungal communities and glomalin-related soil proteins underlie divergent drought responses in indica and japonica rice - Sihan ZHOU; Yanhan JI; Junguo BI; Jiaxuan XU; Jingrui QIU; Xiaoqin ZENG; Zixian JIA; Zijin BIAN; Ning LING; Shuai ZHAO; Sheng ZHOU; Lijun LUO; et al. (Pedosphere, 2026)

Effects of dry-direct seeding with non-flooded regime on starch structure and functionality in water-saving and drought-resistance rice - Danping Hou; Kun Liu; Juncai Li; Li Ma; Yang Wang; Dahu Chen; Wenjiang Jing; Zhihao Chen; Junguo Bi; Lijun Luo (Food Chemistry, 2026)

Engineering boronation mixed-layer coating on polyanion cathode material with self-driven electronic reconstruction for long-life sodium-ion batteries - Hongwei Bi; Ruiyi Li; Xia Sun; Xiaoen Wang; Dan Luo; Zhongwei Chen (Chemical Engineering Journal, 2026)

Tissue-Resident Macrophage PIEZO1 Transduces Mechanical Stress into Inflammatory Pain in Acute Gout - Tianyi Shen; Ting Wang; Liyan Wu; Zihan Wang; Liqin Gan; Yubin Luo; Cong Liu; Yang Xu; De-An Guo; Qirui Bi; Wanying Wu; Lvyi Chen; et al. (Neuroscience Bulletin, 2026)

Cordycepin inhibits human extravillous trophoblast invasion by suppressing snail-mediated MMP2 expression - Manman Guo; Siwei Luo; Beibei Bi; Xiaoyu Han; Yuanyuan Jia; Jung-Chien Cheng; Lanlan Fang (Tissue and Cell, 2026)

Dynamic changes and functional analysis of the vaginal microbial communities in reproductively dysfunctional giant pandas - Xin Chen; Ling Dao; Wenjun Huang; Bi Li; Xiaolan Wang; Zhengyu Chen; Fangfang Liu; Li Luo; Fan Xu (The Veterinary Journal, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Hierarchical porous hollow HZSM-5 catalyst for waste plastic upcycling to aromatics oil via synergistic optimization of pore structure and acidic sites - Yuejin Zhan; Bi Luo; Jiaying Chen; Vasilevich Sergey Vladimirovich; Bilainu Oboirien; Qingang Xiong; Yefeng Zhou (Fuel, 2026)

Highly-selective extraction of lithium from low-quality brines through β-diketone-anchored porous microspheres - Feng Liu; Shimao Xue; Shijie Zhang; Xiaoling Zeng; Peng Zha; Shicong Chen; Sihui Li; Haotian Zhu; Feihu Bi; Liming Yang; Guang Yang; Xubiao Luo; et al. (Chemical Engineering Journal, 2026)

Projected seawater inundation induced by land subsidence will weaken the coastal carbon sink effect - Zhixiong Tang; Rongrong Ning; Fubin Luo; Shilei Peng; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; De Wang (CATENA, 2026)

Phytochemical constituents of the branches and leaves of Callicarpa pedunculata R. Br. and their taxonomic distribution - Chenyu Guo; Yimiao Chen; Limin Chen; Feifei Bi; Xinying Zhang; Ruiying Liu; Keying Xu; Antao Luo; Dan Yan; Guijuan Zheng (Biochemical Systematics and Ecology, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Influence of filling station model-induced turbulence on hydrogen cloud explosion characteristics and overpressure attenuation behavior - Yifei Liu; Qiuhong Wang; Hu Wen; Zhenmin Luo; Bin Peng; Wei Gao; Zhenbao Li; Mingshu Bi; Siru Wang; Siyuan Wu (Process Safety and Environmental Protection, 2026)

Quantitative determination for multiple indicators of lard using machine learning and Raman spectroscopy: A PCA-KNN-based framework with automated optimization of hyperparameters - Zixin Ma; Zhuangwei Shi; Xiaohong Liang; Jianchen Zi; Chenhui Wang; Yongkun Luo; Hai Bi; Shi-Chen Su; Yunhao Su (Food Control, 2026)

Process intensification driven by non-conventional energy fields in emerging plastic recycling: A systematic review - Yuejin Zhan; Yeping Xie; Jiaying Chen; Bi Luo; Lijuan Men; Qianli Wang; Jinxing Chen; Yefeng Zhou (Chemical Engineering Journal, 2026)

Linking soil organic carbon and viral communities in alpine grasslands - Wenyin Wang; Xiaochun Wang; Lingyan Qi; A. Allan Degen; Mei Huang; Binyu Luo; Zheru Zhang; Tianyun Qi; Shuai Qi; Sisi Bi; Chunying Li; Jinfeng Yue; et al. (Plant and Soil, 2026)

The epigenetic and epitranscriptomic regulation of Brd4-Mettl3 axis on STING mediated vascular calcification - Junyong Zhao; Xiaolin Luo; Zelan Wang; Wenjian Luo; Shaofa Wu; Xingyu Ma; He Liu; Yang Chen; Shixian Pi; Jiawen Zhang; Jihang Zhang; Chuan Liu; et al. (Inflammation Research, 2026)

Investigating the Anti-suffusion Capacity of Granular Soils with Different Consolidation Pressures Using Coupled CFD-DEM - Pingfan Wang; Jinfeng Bi; Xianqi Luo; Yunwei Shi; Zhuomin Li (Geotechnical and Geological Engineering, 2026)

Advanced oxidation processes for emerging contaminant removal: A focus on peracetic acid activation and sulfadiazine degradation - Nabi Bux; Xin Wang; Danruo Luo; Mengfei Bi; He Guo; Sadam Hussain Tumrani; Razium Ali Soomro; Iqra Aslam; Kallaya Suntornvongsagul; Qiuling Ma; Jian Zhou; Tiecheng Wang (Journal of Water Process Engineering, 2026)

Microenvironment engineering for enhancing catalytic active sites for the CO oxidation reaction - Menghe Lou; Li Xiang; Guo Nie; Xueqing Luo; Renna Li; Feng Bi; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2026)

Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Coupled nitrogen–pollutant photochemistry: Marine nitration of ethylparaben and formation of toxic nitro-products - Yanpeng Gao; Yi Chen; Suling Wei; Yashi Bi; Yujie Chen; Guanhui Chen; Xiaolin Niu; Na Luo; Yuemeng Ji; Yang-Guang Gu (Water Research, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

Enhanced sequential soil moisture estimation using an ensemble deep learning filter without linear-Gaussian constraints - Tuantuan Zhang; Jianxia Chang; Jiangjiang Zhang; Quanxi Shao; Ranjan Sarukkalige; Zengliang Luo; Chenglin Bi; Jun Wang; Yiming Hu; Binquan Li; Zhongmin Liang (Journal of Hydrology, 2026)

Wake evolution and vacuum length in granular flows impacting obstacles: DEM simulations and analytical solutions - Yi-Han Wu; Zhi-Yuan Zhu; Lu Zheng; Dong-Po Wang; Gang Luo; Yu-Zhang Bi (Computers and Geotechnics, 2026)

Biomimetic microneedle patch integrating ROS-scavenging nanoceria, anti-inflammatory phytochemical, and macrophage-membrane-coated nanoparticles for local hepatic therapy of endotoxemia - Bingwen Zhu; Chang Sun; Dongrong Luo; Zhongliang Zhang; Linguo Cao; Tao Bi; Aolin Jiang; Yuying Liang; Zehui Jiang; Haihua Luo; Pin Jiang; Shaoqing Liu; et al. (Chemical Engineering Journal, 2026)

Nanoparticle-free dualmodal lateral flow immunoassay for sensitive detection of aflatoxin B1 based on “four-in-one” multifunctional nanobody - Tingting Gong; Weili Shen; Kaiyuan Chen; Meng Bi; Cong Liu; Hao Zheng; Wenjia Niu; Yulin Mao; Changli Shao; Longlong Luo; Tieqiang Sun (Analytica Chimica Acta, 2026)

Climate policy uncertainty and the co-movement between clean energy and metal markets: A spillover perspective - Zhiwei Bi; Qiaosheng Wu; Lulu Luo (Resources Policy, 2026)

Integrated utilization design of ore and material: Preparation of nickel-based layered double hydroxides by extracting nickel from pentlandite and doping Fe to improve photocatalytic hydrogen production performance - Xiaolong Bi; Wenning Mu; Anlu Wei; Zhigang Hou; Mengjie Han; Xuefei Lei; Shaohua Luo (Process Safety and Environmental Protection, 2026)

Probiotic strain identification and safety assessment of unlabeled bacteria in infant products - Nanlan Wang; Yarong Wu; Yang Liu; Qian Wen; Fan Bai; Yafang Tan; Yujun Cui; Xingyin Liu; Yujing Bi; Ruifu Yang; Peng Luo (International Journal of Food Microbiology, 2026)

Presence and sources of antibiotics in Dongzhai Harbor, Hainan Island - Tuan-Tuan Wang; Hong-Jin Zhang; Tuan-Qi Guo; Jia-Yu Luo; Bi-Jiao Li; Wen-Qing Liao; Ling Mo; Sai Wang; Yue-Hua Huang (Marine Pollution Bulletin, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

High-humidity hot air impingement blanching (HHAIB): A novel strategy to reconcile drying efficiency and quality preservation in edible cricket processing - Jiaxin He; Xiaotong Fan; Lei Li; Shenyuan Quan; Shiye Luo; Jiabao Ni; Yanxiang Bi; Na Li; Ruge Cao; Xiaoming Fang (Food Chemistry, 2025)

Toxicokinetics of typical halogenated organic pollutants (HOPs) in frogs (Rana tigrina cantor) via skin exposure and effects of hibernation - Ke-Lan Guan; Xiao-Jun Luo; Chu-Hong Zhu; Jian Guo; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

Phospholipid-inspired underwater adhesives achieving fast, durable, and harsh-condition bonding - Xiaoqian Bi; Shaoyu Luo; Zhenxuan Liang; Wenfan Yu; Junfang Xue; Shifeng Zhang; Anmin Huang; Songwu Chen (Chemical Engineering Journal, 2025)

Site-specific substitution strategy for poisoning-resistant of ZrCo-based hydrogen isotope storage alloys - Shunrui Xiao; Jiacheng Qi; Jiapeng Bi; Fei Chu; Qianwen Zhou; Xiulin Fan; Jiahuan He; Xingwen Feng; Huaqin Kou; Xuezhang Xiao; Tao Tang; Wenhua Luo; et al. (Chemical Engineering Journal, 2025)

Balancing water efficiency and crop productivity: rhizosphere microbiome shifts in drought-resistant rice - Junguo Bi; Jiayi Li; Saeed ur Rahman; Yuchong Long; Nan Hui; Martin Romantschuk; Junqiang Zheng; Xianxian Zhang; Danping Hou; Jinsong Tan; Qingyu Bi; Hui Xia; et al. (World Journal of Microbiology and Biotechnology, 2025)

Effects of PM2.5 Reduction Interventions on Cardiovascular Indicators: A Meta-analysis - Qin Liu; Fenglin Xu; Ping Zhang; Xi Zheng; Fanying Xiang; Shunqing Luo; Shenying Fang; Xizhou An; Yang Bi; Jingyu Chen; Yang Gao; Shihai Zheng; et al. (Cardiovascular Toxicology, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Species- and sex-specific bioaccumulation, tissue-specific distribution, and maternal transfer of per- and polyfluoroalkyl substances in tiger frogs (Hoplobatrachus chinensis) and forest frogs (Rana chensinensis) - Chu-Hong Zhu; Xiao-Jun Luo; Xi Chen; Peng-Peng Chen; Ke Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Research, 2025)

Lightweight and high-strength wood composite with asymmetric structure design - Shaoyu Luo; Zhenxuan Liang; Xiaoqian Bi; Wenfan Yu; Jinbo Wang; Zhili Xu; Shifeng Zhang (Chemical Engineering Journal, 2025)

Numerical simulation and experimental investigation of an annular tank filled with Zr0.8Nb0.2Co0.6Cu0.15Ni0.25 hydrogen isotope storage alloy - Liyang Shu; Jiacheng Qi; Liujun Zhan; Zhipeng Li; Yang Liu; Jiapeng Bi; Yongpeng Chen; Panpan Zhou; Zhiyi Yang; Xingwen Feng; Huaqin Kou; Changan Chen; et al. (Chemical Engineering Journal, 2025)

Amine-functionalized polysiloxane-engineered cellulose foam with Ag/MnO2 schottky interfaces for synergistic adsorption-photocatalytic formaldehyde elimination - Wenfan Yu; Shaoyu Luo; Zhenxuan Liang; Wentao Liu; Xiaoqian Bi; Shifeng Zhang; Taiquan Jin (Carbohydrate Polymers, 2025)

Nuclearporin subcomplex Nup98/Rae1 is vital for maternal-to-zygotic transition during early embryonic development - Luo Anfeng; Gu Hao; Akhtar Ali; Qi Mengfan; Pan Kaixin; Zhou Changfan; Zeng Wei; Liu Song; Ren Hongyan; Bi Yanzhen; Chen Fan (Theriogenology, 2025)

Biotransformation causes the sex-specific regulation of polychlorinated biphenyls during metamorphosis of silkworm (Bombyx mori) and their effect on the silkworm development - Xue-Meng Qi; Xiao-Jun Luo; Pei-Xin Su; Peng-Peng Chen; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Effects of hibernation on the bioaccumulation and tissue distribution of per- and polyfluoroalkyl substances in frogs (Rana tigrina cantor) via skin exposure - Chu-Hong Zhu; Xiao-Jun Luo; Ke-Lan Guan; Jian Guo; Peng-Peng Chen; Xi Chen; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

Corrigendum to “Mechanically and functionally strengthened tissue adhesive of chitin whisker complexed chitosan/dextran derivatives based hydrogel” [Carbohydr. Polym. 237 (2020) 116138] - Jianhui Pang; Shichao Bi; Tiantian Kong; Xin Luo; Zhongzheng Zhou; Kaijin Qiu; Liang Huang; Xiguang Chen; Ming Kong (Carbohydrate Polymers, 2025)

Monitoring of yellow leaf disease (YLD) damage based on ground-based LiDAR and UAV multispectral data - Xudong Zhang; Peiyun Bi; Quan Zhou; Li Liu; Lili Ren; Youqing Luo (Computers and Electronics in Agriculture, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Assessing the methane mitigation potential of biochar and stover incorporation: Insights from the emission dynamics and soil microbiome in maize agroecosystems - Xu Yang; Jun Yuan; Yinghui Bi; Lidan Wang; Junqi Zhang; Chaoqun Wei; Xin Cui; Han Li; Peiyu Luo; Jun Meng; Wenfu Chen (Soil and Tillage Research, 2025)

Rupture mechanism of a liquefied gas storage tank in fire and occurrence prediction of a BLEVE - Weiye Luo; Xingtao Dai; Jingjie Ren; Bing Han; Yan Liu; Jun Hu; Mingshu Bi (Process Safety and Environmental Protection, 2025)

Impacts of prolonged power interruption on methane production in MEC-AD systems: Processes and mechanisms - Ling Wang; Chenxin Zhu; Haichao Luo; Xiaoqiu Lin; Yue Ma; Xuejun Bi; Wenzong Liu; Heliang Pang (Chemical Engineering Journal, 2025)

Corrigendum to “Thermo/photo dual-crosslinking chitosan-gelatin methacrylate hydrogel T with controlled shrinking property for contraction fabrication” [Carbohydrate Polymers 236 (2020) 116067] - Xin Luo; Yidan Liu; Jianhui Pang; Shichao Bi; Zhongzheng Zhou; Zhe Lu; Chao Feng; Xiguang Chen; Ming Kong (Carbohydrate Polymers, 2025)

A comprehensive review of rheological behaviors of asphalt binders, mastics, and mixtures from a generalized rheology perspective - Yanqiu Bi; Hao Chen; Zixuan Chen; Jianzhong Pei; Jiupeng Zhang; Zhongbin Luo; Weina Wang; Junfeng Gao (Fuel, 2025)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

Soil Cd bioavailability, enrichment in raw/cooked rice, transfer to gastrointestinal tract and human health risk: A comparative study in mining-impacted non-karst and karst areas - Jue Bi; Huijuan Zhang; Ziwen Luo; Qin Huan; Xue Liu (Environmental Pollution, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Inhibitory effect and mechanism of lipopeptide Iturin A on food spoilage yeasts - Zhemin Li; Wencheng Jiao; Xiufang Bi; Xinyao Xie; Dan Shu; Di Luo; Jie Yang; Zhiying Yan; Hong Tan (Food Bioscience, 2025)

Production of fucose-rich exopolysaccharides by UV-mutated Enterobacter: Optimization, structural characterization and functional properties - Zhemin Li; Shuning Ren; Xiufang Bi; Dan Shu; Di Luo; Jie Yang; Xin Li (Food Bioscience, 2025)

Capacitance deionization pre-lithiation strategy enables upgrading of spent anode graphite via defect engineering - Lijuan Men; Bi Luo; Likai Zhu; Shuyao Feng; Heng Guo; Jiafeng Zhang; Yefeng Zhou (Chemical Engineering Journal, 2025)

Flotillin- 1 ameliorates experimental diabetic retinopathy by inhibiting ferroptosis in blood-retinal barrier - Jie Zhang; Ke Chang; Yanyu Shangguan; Ruoning Luo; Yanlong Bi; Zicheng Yu; Bing Li (Journal of Molecular Medicine, 2025)

Biofouling-resistant tannin/amidoxime functionalized fibers for long-term uranium extraction from seawater - Yi Tang; Zihe Li; Wei Luo; Xuepin Liao; Bi Shi (Desalination, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Activation of Centromedial Amygdala GABAergic Neurons Produces Hypotension in Mice - Xiaoyi Wang; Ziteng Yue; Luo Shi; Wei He; Liuqi Shao; Yuhang Liu; Jinye Zhang; Shangyu Bi; Tianjiao Deng; Fang Yuan; Sheng Wang (Neuroscience Bulletin, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Analysis of the influence of different cuts of pork on the quality and flavor characteristics of Bazi Pork - Jicai Bi; Junyang Zhang; Zhuo Chen; Shuang Jin; Zhen Yang; Qiong Luo; Ke Wang; Yao Zhang; Hongju He (International Journal of Gastronomy and Food Science, 2025)

The optimized nitrogen rate reduced ammonia emissions from rice paddies in the cold region of Northeast China - Shiting Bi; Pengfei Li; Jiarui Lv; Qiang Dong; Xiangyu Luo; Yeqi Che; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (European Journal of Agronomy, 2025)

Extraction of copper from chalcopyrite by clean and efficient chlorination process to prepare Cu-Fe bimetallic oxide for Li-ion batteries: A facile method in view of sustainable engineering - Xiaolong Bi; Wenning Mu; Anlu Wei; Mengjie Han; Xuefei Lei; Qing Wang; Shaohua Luo (Chemical Engineering Journal, 2025)

Antarctic Sea Ice Extraction for Remote Sensing Images via Modified U-Net Based on Feature Enhancement Driven by Graph Convolution Network - Wu Feng; Xiulin Geng; Xiaoyu He; Miao Hu; Jie Luo; Meihua Bi (Journal of Marine Science and Engineering, 2025)
Antarctic true-color imagery synthesized using multispectral remote sensing data is effective in reflecting sea ice conditions, which is crucial for monitoring. Deep learning has been explored for sea ice extraction, but traditional convolutional neural network models are constrained by a limited perceptual field, making it difficult to obtain global contextual information from remote sensing images. A novel model named GEFU-Net, a modification of U-Net, is presented. The self-established graph reconstruction module is employed to convert features into graph data and construct the adjacency matrix using a global adaptive average similarity threshold. Graph convolutional networks are utilized to aggregate the features at each pixel, enabling the rapid capture of global context, enhancing the semantic richness of the features, and improving the accuracy of sea ice extraction through graph reconstruction. Experimental results using the sea ice dataset of the Ross Sea in the Antarctic, produced by Sentinel-2, demonstrate that our GEFU-Net achieves the best performance compared to other commonly used segmentation models. Specifically, it achieves an accuracy of 97.52%, an Intersection over Union of 95.66%, and an F1-Score of 97.78%. Additionally, fewer model parameters and good inference speed are demonstrated, indicating strong potential for practical ice mapping applications.

Potential of hyperspectral LiDAR in individual tree segmentation: A comparative study with multispectral LiDAR - Ao Wang; Shuo Shi; Jian Yang; Bowei Zhou; Yi Luo; Xingtao Tang; Jie Du; Sifu Bi; Fangfang Qu; Chengyu Gong; Wei Gong (Urban Forestry & Urban Greening, 2025)

MMP13 as an effective target of an active trifluoromethyl quinazoline compound against osteosarcoma - Chang-hua Zhou; Ting Zhang; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Bi-xue Xu; Heng Luo; Xiao-bin Tian (Toxicology and Applied Pharmacology, 2025)

Surgical dissection of ignition behavior of aluminum nanoparticles using molecular dynamics - Yiming Lu; Lili Ye; Hongxin Luo; Mingshu Bi (Fuel, 2025)

The bioaccessibility and bioactivity of polyphenols from tsampa prepared from roasted highland barley flour solid-fermented by autochthonous lactic acid bacteria - Nuo Chen; Wenming Dong; Qin Luo; Yonghua Huang; Bi Chen; Hu Wang; Nannan Ren; Ling yuan Luo; Yongqiang Li (Food Research International, 2025)

Comprehensive Analysis Based on the TCGA Database Identified SCIN as a Key DNA Methylation-Driver Gene in Epstein-Barr Virus-Associated Gastric Cancer - Zhiyuan Gong; Chunxia Bi; Wen Liu; Bing Luo (Biochemical Genetics, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Features of particle-phase PAHs from traffic emissions using tunnel measurement and urban roadside observation in China - Fei Gao; Zhitao Cai; Zhenyu Luo; Junchao Zhao; Songxin Zheng; Li Wang; Bi Chen; Kebin He; Huan Liu (Environmental Pollution, 2025)

Constructing azobenzene-decorated Ni-MOF toward efficient oxygen evolution reaction - Mingbiao Luo; Xingyu Liu; Liu Yang; Zhenzhen Xu; Yuan Tao; Qingsheng Huang; Sijia Lv; Peiyan Bi; Zhi Gao (Chemical Engineering Journal, 2025)

CdS/NiCoAl-LDH heterojunction for superior photocatalytic hydrogen production and stability in water splitting - Ruimin Yang; Wenning Mu; Longyan He; Junjin Meng; Xiaolong Bi; Wenbin Luo; Shaohua Luo; Xuefei Lei (Chemical Engineering Journal, 2025)

Quality control and improvement of GNSS-IR soil moisture robust inversion model - Yijie Li; Linyu Luo; Fei Guo; Furong Yang; Tianyang Wang; Hang Gao; Xinyu Bi; Zhitao Zhang; Yifei Yao (Advances in Space Research, 2025)

Effect of yeast (Saccharomyces cerevisiae) fermentation on conformational changes in pig liver proteins and their ability to bind to characteristic aldehydes - Jin Luo; Li Liang; Jingcheng Zhang; Yongzhao Bi; Rui Yang; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2024)

Insights into the sunlight-Induced photodegradation mechanisms of methamphetamine in surface water driven by NO₃⁻, HCO₃⁻ and Fe3+ - Lijuan Luo; Junhui Wu; Xueting Yuan; Xinyan Li; Bi Huang; Shanshan Chen; Jiewei Deng; Tiangang Luan (Environmental Pollution, 2024)

Thyroid hormones and oxidative stress moderated the association between urinary phthalate metabolites and cardiovascular risk factors - Rong He; Hua Bi; Jia He; Yangxu Luo; Xiaotong Li; Qin Li; Rende Huang; Lei Tan (Environmental Pollution, 2024)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Identification of key genes of diabetic cardiomyopathy in hiPSCs-CMs based on bioinformatics analysis - Shuo An; Hongchen Bi; Xiaoli Luo; Caiying Zhu; Min Wang; Aiming Pang; Yujie Cui (Molecular and Cellular Biochemistry, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Unveiling Cloud Vertical Structures over the Interior Tibetan Plateau through Anomaly Detection in Synergetic Lidar and Radar Observations - Wei Zhao; Yinan Wang; Yongheng Bi; Xue Wu; Yufang Tian; Lingxiao Wu; Jingxuan Luo; Xiaoru Hu; Zhengchao Qi; Jian Li; Yubing Pan; Daren Lyu (Advances in Atmospheric Sciences, 2024)

An alloying element screening method to design Zr2Co based alloys with superior disproportionation resistance - Yang Liu; Xuezhang Xiao; Zhiyi Yang; Fei Chu; Panpan Zhou; Jiapeng Bi; Tiao Ying; Xingwen Feng; Jiangfeng Song; Yan Shi; Changan Chen; Wenhua Luo; et al. (Chemical Engineering Journal, 2024)

Modification of Prussian blue analogues as high-performance cathodes for sodium-ion batteries - Yifan Huang; Wenning Mu; Junjin Meng; Xiaolong Bi; Xuefei Lei; Shaohua Luo (Chemical Engineering Journal, 2024)

A comprehensive review of plant-derived salt substitutes: Classification, mechanism, and application - Yongzhao Bi; Li Liang; Kaina Qiao; Jin Luo; Xialei Liu; Baoguo Sun; Yuyu Zhang (Food Research International, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Nontarget analysis and characterization of p-phenylenediamine-quinones and -phenols in tire rubbers by LC-HRMS and chemical species-specific algorithm - Caiming Tang; Yizhe Zhu; Ruifen Zheng; Ling Liu; Yan-Hong Zeng; Xiao-Jun Luo; Bi-Xian Mai (Analytica Chimica Acta, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Three new furanones from endophytic fungus Hypoxylon vinosopulvinatum DYR-1-7 from Cinnamomum cassia with their antifungal activity - Jia Lv; Hong Zhou; Limei Dong; Hao Wang; Li Yang; Haiqian Yu; Peixi Wu; Le Zhou; Quan Yang; Yongqian Liang; Bi Luo (Natural Product Research, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Asynchronous hydroclimate variability in Northeast Asia during the last millennium - Anze Chen; Xin Zhou; Shiwei Jiang; Yong Luo; Xuanqiao Liu; Junchi Liu; Xiangzhong Li; Zhenhao Wu; Min Ding; Xiaolin Zhang; Liqiang Xu; Ming Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Engineering “three-in-one” fluorescent nanozyme of Ce-Au NCs for on-site visual detection of Hg2+ - Lijun Luo; Jiamin Li; Xiaoya Bi; Panao Jiang; Libo Li; Guanjun Qiao; Tianyan You (Journal of Hazardous Materials, 2024)

In vivo RNAi screening identifies multiple deubiquitinases required for the maintenance of intestinal homeostasis in Drosophila - Boyu Zhao; Jing Luo; Hui Wang; Yuanxin Li; Dong Li; Xiaolin Bi (Insect Biochemistry and Molecular Biology, 2024)

Lignin-Assisted local release of triiodothyronine in adipose tissue protects mice against obesity and related metabolic disorders - Guangyan Wang; Ya Ma; Xiaoyu Zhao; Lingjuan Luo; Wenjing Xiu; Zhicheng Jiang; Bi Shi; Chunjiong Wang (Chemical Engineering Journal, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

Suppressing lithium dendrite via hybrid interface layers for high performance quasi-solid-state lithium metal batteries - Bi Luo; Qi Wang; Weijie Ji; Guihui Yu; Zaowen Zhao; Ruirui Zhao; Bao Zhang; Xiaowei Wang; Jiafeng Zhang (Chemical Engineering Journal, 2024)

Characteristics of number concentration, size distribution and components of particulate matter emitted from a typical large civil airport - Sihan Yin; Zhichao Lu; Yufei Zhang; Lilai Song; Shenyu Bi; Xi Luo; Lu Yao; Xiaohui Bi; Han Bo; Yinchang Feng (Science of The Total Environment, 2024)

Seed Priming with Gibberellic Acid and Ethephon Improved Rice Germination under Drought Stress via Reducing Oxidative and Cellular Damage - Kangkang Zhang; Mohammad Nauman Khan; Tao Luo; Junguo Bi; Liyong Hu; Lijun Luo (Journal of Soil Science and Plant Nutrition, 2024)

Quantification of NOx sources contribution to ambient nitrate aerosol, uncertainty analysis and sensitivity analysis in a megacity - Wenhui Zhang; Fuliang Wu; Xi Luo; Lilai Song; Xuehan Wang; Yufen Zhang; Jianhui Wu; Zhimei Xiao; Fang Cao; Xiaohui Bi; Yinchang Feng (Science of The Total Environment, 2024)

Study on dynamic behavior and crack propagation mechanism of the tanks in one-step BLEVE accident - Weiye Luo; Jingjie Ren; Di Yu; Zilong Deng; Mingshu Bi (Process Safety and Environmental Protection, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Insights into the occurrence, spatial distribution, and ecological implications of organophosphate triesters in surface sediments from polluted urban rivers across China - Yin-E Liu; Xiao-Jun Luo; Chen-Chen Huang; Qihong Lu; Shanquan Wang; Bi-Xian Mai (Science of The Total Environment, 2024)

Estuarine groundwater level response to and recovery from extreme precipitation events: Typhoon Lekima in the Yellow River Delta - Fubin Luo; De Wang; Xinpeng Tian; Xiaoli Bi; Qian Zheng; Zixiang Zhou; Zhixiong Tang (Journal of Hydrology, 2024)

Effects of ignition position and hydrogen concentration on the flame propagation characteristics of hydrogen–air deflagration - Qiuhong Wang; Hongxiang Wan; Mingshu Bi; Wei Gao; Bin Peng; Zhenmin Luo; Jian Chen; Yunfan Xue (Fuel, 2024)

NH3 plasma synthesis of amino modified NiCo layered double hydroxide nanoflowers for carbon dioxide photoreduction - Yanhua Song; Zeen Zheng; Jiao Luo; Hangmin Xu; Kang Zhong; Anqi Zhou; Hao Song; Chuanzhou Bi; Jinman Yang; Md Shouquat Hossain; Hui Xu; Xingwang Zhu (Journal of Environmental Chemical Engineering, 2024)

A comprehensive assessment of external exposure to persistent halogenated organic pollutants for residents in an e-waste recycling site, South China - Yin-Zhi Lv; Xiao-Jun Luo; Xue-Meng Qi; Ke-Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2024)

Transboundary transport of non-east and East Asian dust observed at Dunhuang, northwest China - Tian Zhou; Xiaowen Zhou; Zining Yang; Carmen Córdoba-Jabonero; Yufei Wang; Zhongwei Huang; Pengbo Da; Qiju Luo; Zhijuan Zhang; Jinsen Shi; Jianrong Bi; Hocine Alikhodja (Atmospheric Environment, 2024)

The Protocol of Ultrasonic Backscatter Measurements of Musculoskeletal Properties - Dongsheng Bi; Lingwei Shi; Boyi Li; Ying Li; Chengcheng Liu; Lawrence H. Le; Jingchun Luo; Sijia Wang; Dean Ta (Phenomics, 2024)

Transfer of heavy metals from soil to tea and the potential human health risk in a regional high geochemical background area in southwest China - Yongwang Ju; Ziwen Luo; Jue Bi; Chaozhu Liu; Xue Liu (Science of The Total Environment, 2024)

Bioaccumulation, tissue distributions, and maternal transfer of perfluoroalkyl carboxylates (PFCAs) in laying hens - Qun-Jie Feng; Xiao-Jun Luo; Mei-Xia Ye; Ke-Qi Hu; Yan-Hong Zeng; Bi-Xian Mai (Science of The Total Environment, 2023)

Ligand-engineered Ni-based metal–organic frameworks for electrochemical oxygen evolution reaction - Zhenzhen Xu; Yuan Tao; Zhaodi Sun; Peiyan Bi; Xing Zhong; Jiajun Liao; Dacheng Hao; Licheng Yang; Lin Xu; Mingbiao Luo; Kecheng Pan; Zhi Gao (Chemical Engineering Journal, 2023)

Rapid Genotyping of Campylobacter coli Strains from Poultry Meat by PFGE, Sau-PCR, and fla-DGGE - Ge-Feng Yao; Yi-Lin Hu; Nian-Qing Kong; Jin-Hong Liu; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Current Microbiology, 2023)

The impact of freezing methods on the quality, moisture distribution, microstructure, and flavor profile of hand-grabbed mutton during long-term frozen storage - Yulong Luo; Yongzhao Bi; Rui Du; Hong Yuan; Yanru Hou; Ruiming Luo (Food Research International, 2023)

A novel integrated automatic strategy for amino acid composition analysis of seeds from 67 species - Yelin Ding; Qirui Bi; Dongdong Huang; Jingmei Liao; Lin Yang; Xiaoxiao Luo; Peilei Yang; Yun Li; Changliang Yao; Wenlong Wei; Jianqing Zhang; Jiayuan Li; et al. (Food Chemistry, 2023)

Label-free quantitative proteomic analysis of milk fat globule membrane proteins in porcine colostrum and mature milk - Huiwen Zhao; Mohan Li; Qing Zhu; Aicheng Liu; Jiayang Bi; Zhizhong Quan; Xue Luo; Yan Zheng; Ning Yang; Xiqing Yue; Xueyan Cao (Food Chemistry, 2023)

Organophosphate diesters (DAPs) and hydroxylated organophosphate flame retardants (HO-OPFRs) as biomarkers of OPFR contamination in a typical freshwater food chain - Yin-E Liu; Xiao-Jun Luo; Hong-Chang Ding; Lin Qi; Bin Tang; Bi-Xian Mai; Giulia Poma; Adrian Covaci (Chemosphere, 2023)

Suitability evaluation of rural sewage treatment facilities in China considering lifcycle environmental impacts and regional differences - Jiping Jiang; Xiao Hu; Yang Gu; Wenzhao Wang; Zhaoshun Bi; Changsong Yao; Xiao Liang; Qingzhi Wen; Meiyu Luo; Yi Zheng; Xunfeng Xia (Journal of Environmental Management, 2023)

Identification of two galectin-4 proteins (PcGal4-L and PcGal4-L-CRD) and their function in AMP expression in Procambarus clarkii - Tingyi Luo; Xianfeng Ren; Lixia Fan; Changying Guo; Bingchun Zhang; Jingxiu Bi; Shuai Guan; Mingxiao Ning (Fish & Shellfish Immunology, 2023)

Multi-factor coupling analysis and identification of tanks BLEVE - Weiye Luo; Mingshu Bi; Yue Zhang; Di Yu; Zilong Deng; Jingjie Ren (Process Safety and Environmental Protection, 2023)

Gold nanocluster-confined covalent organic frameworks as bifunctional probes for electrochemiluminescence and colorimetric dual-response sensing of Pb2+ - Libo Li; Wanlin Zhao; Yan Wang; Xiaohong Liu; Panao Jiang; Lijun Luo; Xiaoya Bi; Xiangle Meng; Qijian Niu; Xiaofeng Wu; Tianyan You (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Impacts of bedding angle and cementation type of bedding planes on mechanical behavior of thin-layer structured bedded rocks under uniaxial compression - Minghui Liu; Xinyao Luo; Ruiyang Bi; Jian Zhou; Kun Du (Geomechanics for Energy and the Environment, 2023)

Correlating severe land subsidence and confined brine aquifer compaction in the Yellow River Delta, China, with Sentinel-1A/1B satellite images - Yi Zhang; Yafei Luo; Haijun Huang; Yanxia Liu; Haibo Bi; Xinyuan Zhang; Zehua Zhang; Kuifeng Wang; Zechao Bai; Xinghua Zhou (Marine Georesources & Geotechnology, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Selective extraction of gold from strong acid E-waste leachate through H+-triggered cascade reaction of thiolated β-cyclodextrin - Difan Fang; Feihu Bi; Liming Yang; Wenbin Hu; Zan Hua; Hanchen Wei; Changli Chen; Yunyun Tu; Penghui Shao; Min Li; Xubiao Luo; Guang Yang (Resources, Conservation and Recycling, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Shewanella subflava sp. nov., a novel multi-resistant bacterium, isolated from the estuary of the Fenhe River into the Yellow River - Bi Luo; Jing-Yun Su; Ya-Nan Wang; Li Guan; Kai-Shi Dong; Hui-Jing Niu; Shao-Fei Shen; Yi Li (Antonie van Leeuwenhoek, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

Molecular engineering of Fe-MIL-53 electrocatalyst for effective oxygen evolution reaction - Yue Wang; Zhiyi Zhou; Yuzhi Lin; Yongzheng Zhang; Peiyan Bi; Qiqi Jing; Yidong Luo; Zhaodi Sun; Jiajun Liao; Zhi Gao (Chemical Engineering Journal, 2023)

Large-scale moisture transport and local-scale convection patterns associated with warm-sector heavy rainfall over South China - Guicai Ning; Ming Luo; Xueyan Bi; Zhizhao Liu; Hui Zhang; Meng Huang; Xiaogang Huang; Yuanjian Yang; Sijia Wu (Atmospheric Research, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Facilitating ionic conductivity and interfacial stability via oxygen vacancies-enriched TiO2 microrods for composite polymer electrolytes - Bi Luo; Weigang Wang; Qi Wang; Weijie Ji; Guihui Yu; Zihang Liu; Zaowen Zhao; Xiaowei Wang; Shubin Wang; Jiafeng Zhang (Chemical Engineering Journal, 2023)

γ-Glutamylcysteine rescues mice from TNBS-driven inflammatory bowel disease through regulating macrophages polarization - Jinyi Zhou; Xintong Yan; Xiaowen Bi; Shuai Lu; Xianli Liu; Chen Yang; Yingying Shi; Lan Luo; Zhimin Yin (Inflammation Research, 2023)

Occurrence, spatial distribution, and risk assessment of short- and medium-chain chlorinated paraffins in sediment from black-odorous rivers across China - Ke-Lan Guan; Xiao-Jun Luo; Qi-Hong Lu; Chen-Chen Huang; Xue-Meng Qi; Yan-Hong Zeng; Bi-Xian Mai; Shan-Quan Wang (Chemosphere, 2023)

Sensitivity and uncertainties assessment in radiative forcing due to aerosol optical properties in diverse locations in China - Fuquan Lu; Siyu Chen; Zeyong Hu; Zhiwei Han; Khan Alam; Hongyu Luo; Hongru Bi; Junyan Chen; Xinyang Guo (Science of The Total Environment, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

A flexible zinc ion hybrid capacitor integrated system with layers-dependent V2CTx MXene - Sairao Zhao; Xiao Luo; Yongfa Cheng; Zhixiang Shi; Tao Huang; Shanghua Yang; Haojian Zheng; Yun Bi; Jun Zhang; Qiuyue Shi; Minglei Cao; Chuankun Zhang; et al. (Chemical Engineering Journal, 2023)

Cerium Oxide Nanoparticles Promote Osteoplastic Precursor Differentiation by Activating the Wnt Pathway - Junchao Luo; Senbo Zhu; Yu Tong; Yin Zhang; Yong Li; Li Cao; Mingxiang Kong; Min Luo; Qing Bi; Qiong Zhang (Biological Trace Element Research, 2023)
Osteoplastic precursors are critical for fracture repair and bone homeostasis maintenance. Cerium oxide nanoparticles (CeO 2 NPs) can promote the osteogenic differentiation of mesenchymal stem cells and secrete vascular endothelial growth factors. However, little is known about its role in precursor osteoblasts; therefore, we further investigated the effect and mechanism of CeO 2 NPs in precursor osteoblasts. Cell counting kit-8 analysis was utilized to detect the toxicity of CeO 2 NPs on MC3T3-E1 mouse osteogenic precursor cells. Then, alizarin red S staining was employed to assess the degree of extracellular matrix mineralization, and quantitative real-time polymerase chain reaction analysis was performed to measure the levels of osteogenesis-related genes. To identify differentially expressed genes, mRNA-sequencing was performed. Subsequently, GO and KEGG analyses were deployed to identify the major downstream pathways, whereas Western blot was used for verification. CeO 2 NPs significantly enhanced the ability of MC3T3-E1 precursor osteoblasts to enhance matrix mineralization and increased the expression of osteogenic genes such as runt-related transcription factor 2, collagen Iα1, and osteocalcin. Pathway analysis revealed that CeO 2 NPs enhanced the nuclear translocation of β-catenin and activated the Wnt pathway by promoting family with sequence similarity 53 member B/simplet expression, while Western blot analysis indicated the same results. After using a Wnt pathway inhibitor (KYA1797K), the simulative effect of CeO 2 NPs was abolished. This study revealed that CeO 2 NPs promoted MC3T3-E1 precursor osteoblast differentiation by activating the Wnt pathway.

ZIF-8-derived Cu, N co-doped carbon as a bifunctional cathode catalyst for enhanced performance of microbial fuel cell - Bi-Lin Lai; Hui-Xu Wei; Zi-Nuo Luo; Tong Zheng; Yi-Hui Lin; Zhao-Qing Liu; Nan Li (Science of The Total Environment, 2023)

Occurrence and distribution of microplastics in coastal plain soils under three land-use types - De Bi; Beibei Wang; Zhu Li; Yabing Zhang; Xin Ke; Chengwang Huang; Wuxing Liu; Yongming Luo; Peter Christie; Longhua Wu (Science of The Total Environment, 2023)

Genesis of the Eocene oxidized potassic felsic volcanic rocks in western Yunnan, China: Insights into mantle redox conditions and post-collisional porphyry Cu–Au formation - Gong Liu; Lei-Luo Xu; Xian-Wu Bi; Jing-Jing Zhu; Zong-Yong Yang; Ming-Liang Huang (Lithos, 2023)

Fetal exposure to organic contaminants revealed by infant hair: A preliminary study in south China - Feng-Shan Cai; Bin Tang; Jing Zheng; Xiao Yan; Wei-Keng Luo; Mian He; Xiao-Jun Luo; Ming-Zhong Ren; Yun-Jiang Yu; Bi-Xian Mai (Environmental Pollution, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Mantle contribution to the generation of the giant Jinduicheng porphyry Mo deposit, Central China: New insights from combined in-situ element and isotope compositions of zircon and apatite - Lei-Luo Xu; Xian-Wu Bi; Xing-Chun Zhang; Ming-Liang Huang; Gong Liu (Chemical Geology, 2023)

High-throughput screening of metal–organic frameworks for hydrogen purification - Shihui Wang; Min Cheng; Lei Luo; Xu Ji; Chong Liu; Kexin Bi; Li Zhou (Chemical Engineering Journal, 2023)

Genesis of hydrous-oxidized parental magmas for porphyry Cu (Mo, Au) deposits in a postcollisional setting: examples from the Sanjiang region, SW China - Lei-Luo Xu; Jing-Jing Zhu; Ming-Liang Huang; Li-Chuan Pan; Ruizhong Hu; Xian-Wu Bi (Mineralium Deposita, 2023)

Comparison of pulsed-field gel electrophoresis and a novel amplified intergenic locus polymorphism method for molecular typing of Campylobacter jejuni - Jin-Hong Liu; Cheng-Lu Lan; Ge-Feng Yao; Nian-Qing Kong; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Archives of Microbiology, 2023)

A new insight into the emission source of DDT in indoor environment from rural area of South China and comprehensive human health exposure assessment - Yin-Zhi Lv; Xiao-Jun Luo; Qi-Qi Li; Yan Yang; Yan-Hong Zeng; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Mitigation of low temperature stress by increased salinity is associated with multiple physiological responses in the gills of Takifugu fasciatus - Sisi Ma; Sheng Luo; Kai Zhang; Yuxi Liu; Xiaozhen Wei; Jinghao Cheng; Yihui Bi; Yiru Sun; Xinyu Zhang; Shaowu Yin; Tao Wang (Marine Biology, 2022)

Sharing of nitrogen between connected ramets of Alternanthera philoxeroides in homogeneous environments - Bi-Cheng Dong; Pu Wang; Fang-Li Luo (Plant and Soil, 2022)

Changes in levels of legacy and emerging organophosphorus flame retardants and plasticizers in indoor dust from a former e-waste recycling area in South China: 2013–2017 - Bin Tang; Christina Christia; Xiao-Jun Luo; Adrian Covaci; Giulia Poma; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

The application prospect of metal/metal oxide nanoparticles in the treatment of osteoarthritis - Junchao Luo; Yin Zhang; Senbo Zhu; Yu Tong; Lichen Ji; Wei Zhang; Qiong Zhang; Qing Bi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
The current understanding of osteoarthritis is developing from a mechanical disease caused by cartilage wear to a complex biological response involving inflammation, oxidative stress and other aspects. Nanoparticles are widely used in drug delivery due to its good stability in vivo and cell uptake efficiency. In addition to the above advantages, metal/metal oxide NPs, such as cerium oxide and manganese dioxide, can also simulate the activity of antioxidant enzymes and catalyze the degradation of superoxide anions and hydrogen peroxide. Degrading of metal/metal oxide nanoparticles releases metal ions, which may slow down the progression of osteoarthritis by inhibiting inflammation, promoting cartilage repair and inhibiting cartilage ossification. In present review, we focused on recent research works concerning osteoarthritis treating with metal/metal oxide nanoparticles, and introduced some potential nanoparticles that may have therapeutic effects.

The exploration of Parkinson’s disease: a multi-modal data analysis of resting functional magnetic resonance imaging and gene data - Xia-an Bi; Hao Wu; Yiming Xie; Lixia Zhang; Xun Luo; Yu Fu (Brain Imaging and Behavior, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Investigating the spatial distribution of polychlorinated biphenyls in sediment in the Pearl River Delta, South China - Man-Ying Chen; Hong-Yin Liu; Xiao-Jun Luo; Bi-Xian Mai; Feng-Hui Lu (Environmental Monitoring and Assessment, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Investigation of the Starting-Up Axial Hydraulic Force and Structure Characteristics of Pump Turbine in Pump Mode - Zhongyu Mao; Ran Tao; Funan Chen; Huili Bi; Jingwei Cao; Yongyao Luo; Honggang Fan; Zhengwei Wang (Journal of Marine Science and Engineering, 2021)
During the starting up of the pump mode in pump turbines, the axial hydraulic force acting on the runner would develop with the guide vane opening. It causes deformation and stress on the support bracket, main shaft and runner, which influence the operation security. In this case, the axial hydraulic force of the pump turbine is studied during the starting up of pump mode. Its influences on the support bracket and main shaft are investigated in detail. Based on the prediction results of axial hydraulic force, the starting-up process can be divided into “unsteady region” and “Q flat region” with obviously different features. The mechanism is also discussed by analyzing pressure distributions and streamlines. The deformation of the support bracket and main shaft are found to have a relationship with the resultant force on the crown and band. A deflection is found on the deformation of the runner with the nodal diameter as the midline in the later stages of the starting-up process. The reason is discussed according to pressure distributions. The stress concentration of the support bracket is found on the connection between thrust seating and support plates. The stress of the runner is mainly on the connection between the crown and the blade’s leading-edge. This work will provide more useful information and strong references for similar cases. It will also help in the design of pump turbine units with more stabilized systems for reducing over-loaded hydraulic force, and in the solving of problems related to structural characteristics.

Modeling of Suffusion Considering the Influence of Soil Gradation - Jinfeng Bi; Xianqi Luo; Hui Shen (Transport in Porous Media, 2021)

Speciation Analysis of Chromium in Chromium-Enriched Yeast by Ion Chromatography-Inductively Coupled Plasma Mass Spectrometry - Shuang-Qing Zhang; Sui-Han Cheng; Shi Shen; Bi-Ying Luo; Yan Zhang (Biological Trace Element Research, 2021)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Submarine slope stability analysis during natural gas hydrate dissociation - Haitao Zhang; Xianqi Luo; Jinfeng Bi; Gaofeng He; Zijing Guo (Marine Georesources & Geotechnology, 2019)

Stability analysis of complex rock slopes reinforced with prestressed anchor cables and anti-shear cavities - Jinfeng Bi; Xianqi Luo; Haitao Zhang; Hui Shen (Bulletin of Engineering Geology and the Environment, 2019)

Adsorption of Cd(II) from aqueous solution by Pennisetum sp. straw biochars derived from different modification methods - Guangcai Yin; Lulin Bi; Xiaowang Song; Haoyu Luo; Pengpeng Ji; Qintie Lin; Qianjun Liu; Guiyou Tang (Environmental Science and Pollution Research, 2019)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Identifying apomixis in matroclinal progeny from an interspecific crossing between Iris domestica and three different colors of Iris dichotoma - Fengyang Yu; Wenji Xu; Yuee Xiao; Gangjun Luo; Qingxiang Jia; Yang Zheng; Xiaoying Bi (Euphytica, 2017)

The acute toxicity of bisphenol A and lignin-derived bisphenol in algae, daphnids, and Japanese medaka - Dan Li; Ran Bi; Hongxing Chen; Lei Mu; Lina Zhang; Qin Chen; Haibo Xie; Yongju Luo; Lingtian Xie (Environmental Science and Pollution Research, 2017)

High-efficient n-butanol production by co-culturing Clostridium acetobutylicum and Saccharomyces cerevisiae integrated with butyrate fermentative supernatant addition - Hongzhen Luo; Qingwei Zeng; Shuo Han; Zhaoyu Wang; Qing Dong; Yanhong Bi; Yuping Zhao (World Journal of Microbiology and Biotechnology, 2017)

Assessment of metal contamination in the Hun River, China, and evaluation of the fish Zacco platypus and the snail Radix swinhoei as potential biomonitors - Xing Wu; Shaofeng Wang; Hongxing Chen; Zhiqiang Jiang; Hongwei Chen; Mi Gao; Ran Bi; Paul L. Klerks; He Wang; Yongju Luo; Lingtian Xie (Environmental Science and Pollution Research, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Conserved and divergent roles of the HOG1 kinase of Alternaria longipes in mycelial and conidial development, multi-stress responses, melanin production and pathogenicity - Zhiqun Yin; Wei Bi; Qili Mi; Ziteng Kang; Chenjian Liu; Jinkui Yang; Yiyong Luo (European Journal of Plant Pathology, 2017)

Timosaponin B-II ameliorates scopolamine-induced cognition deficits by attenuating acetylcholinesterase activity and brain oxidative damage in mice - Xu Zhao; Chunmei Liu; Yu Qi; Lina Fang; Jie Luo; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2016)

Phylogeography of the heavily poached A frican common pangolin (Pholidota, Manis tricuspis ) reveals six cryptic lineages as traceable signatures of Pleistocene diversification - Philippe Gaubert; Flobert Njiokou; Gabriel Ngua; Komlan Afiademanyo; Sylvain Dufour; Jean Malekani; Sery Gonedelé Bi; Christelle Tougard; Ayodeji Olayemi; Emmanuel Danquah; Chabi A. M. S. Djagoun; Prince Kaleme; et al. (Molecular Ecology, 2016)
Knowledge on faunal diversification in African rainforests remains scarce. We used phylogeography to assess (i) the role of Pleistocene climatic oscillations in the diversification of the African common pangolin ( M anis tricuspis ) and (ii) the utility of our multilocus approach for taxonomic delineation and trade tracing of this heavily poached species. We sequenced 101 individuals for two mitochondrial DNA (mt DNA ), two nuclear DNA and one Y‐borne gene fragments (totalizing 2602 bp). We used a time‐calibrated, Bayesian inference phylogenetic framework and conducted character‐based, genetic and phylogenetic delineation of species hypotheses within African common pangolins. We identified six geographic lineages partitioned into western Africa, Ghana, the Dahomey Gap, western central Africa, Gabon and central Africa, all diverging during the Middle to Late Pleistocene. Mt DNA (cytochrome b + control region) was the sole locus to provide diagnostic characters for each of the six lineages. Tree‐based Bayesian delimitation methods using single‐ and multilocus approaches gave high support for ‘species’ level recognition of the six African common pangolin lineages. Although the diversification of African common pangolins occurred during Pleistocene cyclical glaciations, causative correlation with traditional rainforest refugia and riverine barriers in Africa was not straightforward. We conclude on the existence of six cryptic lineages within African common pangolins, which might be of major relevance for future conservation strategies. The high discriminative power of the mt DNA markers used in this study should allow an efficient molecular tracing of the regional origin of African common pangolin seizures.

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

MeHg Suppressed Neuronal Potency of Hippocampal NSCs Contributing to the Puberal Spatial Memory Deficits - Jianying Tian; Yougen Luo; Weiwei Chen; Shengsen Yang; Hao Wang; Jing Cui; Zhiyan Lu; Yuanye Lin; Yongyi Bi (Biological Trace Element Research, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

A novel acetylcholinesterase inhibitor and calcium channel blocker SCR-1693 improves Aβ25–35-impaired mouse cognitive function - Zhengping Zhang; Rong Chen; Wenji An; Chunmei Wang; Gaoyong Liao; Xiaoliang Dong; Aijing Bi; Zhimin Yin; Lan Luo (Psychopharmacology, 2016)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Bioaccumulative characteristics of tetrabromobisphenol A and hexabromocyclododecanes in multi-tissues of prey and predator fish from an e-waste site, South China - Bin Tang; Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bi-Xian Mai (Environmental Science and Pollution Research, 2015)

Impact of Intracranial Artery Disease and Prior Cerebral Infarction on Central Nervous System Complications After Off-Pump Coronary Artery Bypass Grafting - Q. Bi; J.-Yu Li; X.-Q. Li; Q. Li; D. Luo; Q.-B. Qiao (Neurophysiology, 2014)

Developing microsatellite markers for Geodorum eulophioides (Orchidaceae) and cross-species amplification in two sympatric, congeneric species - Ting Ying; Qi-Fang Geng; Dan-Bi Wang; Hong Liu; Jing Xu; Zi-Bing Zhang; Zhong-Sheng Wang; Yi-Bo Luo (Conservation Genetics Resources, 2014)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

Salicylic acid improves chilling tolerance by affecting antioxidant enzymes and osmoregulators in sacha inchi (Plukenetia volubilis) - Y. L. Luo; Z. L. Su; T. J. Bi; X. L. Cui; Q. Y. Lan (Brazilian Journal of Botany, 2014)

Sedum plumbizincicola X.H. Guo et S.B. Zhou ex L.H. Wu (Crassulaceae): a new species from Zhejiang Province, China - L. H. Wu; Y. J. Liu; S. B. Zhou; F. G. Guo; D. Bi; X. H. Guo; A. J. M. Baker; J. A. C. Smith; Y. M. Luo (Plant Systematics and Evolution, 2013)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Permissible Value for Vanadium in Allitic Udic Ferrisols Based on Physiological Responses of Green Chinese Cabbage and Soil Microbes - Xi-yuan Xiao; Miao Yang; Zhao-hui Guo; Yue-ping Luo; Jun-ping Bi (Biological Trace Element Research, 2012)

Phylogenetic analysis of the S1 glycoprotein gene of infectious bronchitis viruses isolated in China during 2009–2010 - Hongbin Luo; Jianping Qin; Feng Chen; Qingmei Xie; Yingzuo Bi; Yongchang Cao; Chunyi Xue (Virus Genes, 2012)

Heavy Metals in Hair of Residents in an E-Waste Recycling Area, South China: Contents and Assessment of Bodily State - Jing Zheng; Xiao-Jun Luo; Jian-Gang Yuan; Luo-Yiyi He; Yi-Hui Zhou; Yong Luo; She-Jun Chen; Bi-Xian Mai; Zhong-Yi Yang (Archives of Environmental Contamination and Toxicology, 2011)

Foot-and-mouth disease virus leader proteinase inhibits dsRNA-induced RANTES transcription in PK-15 cells - Dang Wang; Liurong Fang; Jing Bi; Quangang Chen; Lu Cao; Rui Luo; Huanchun Chen; Shaobo Xiao (Virus Genes, 2011)

Polychlorinated biphenyls and organochlorinated pesticides in birds from a contaminated region in South China: association with trophic level, tissue distribution and risk assessment - Xiu-Lan Zhang; Xiao-Jun Luo; Juan Liu; Yong Luo; She-Jun Chen; Bi-Xian Mai (Environmental Science and Pollution Research, 2011)

Transient characteristics of residual meridional circulation during stratospheric sudden warming - Shumei Deng; Yuejuan Chen; Yong Huang; Tao Luo; Yun Bi (Advances in Atmospheric Sciences, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

Dynamic response of ginsenosides in American ginseng to root fungal pathogens - Xiao Lin Jiao; Wu Bi; Ming Li; Yong Luo; Wei Wei Gao (Plant and Soil, 2011)

Polybrominated Diphenyl Ethers (PBDEs), Polychlorinated Biphenyles (PCBs), Hydroxylated and Methoxylated-PBDEs, and Methylsulfonyl-PCBs in Bird Serum from South China - Juan Liu; Xiao-Jun Luo; Le-Huan Yu; Ming-Jing He; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2010)

Transcriptional responses of Haemophilus parasuis to iron-restriction stress in vitro - Qiyun Xie; Hui Jin; Rui Luo; Yun Wan; Jie Chu; Hufeng Zhou; Bi Shi; Huanchun Chen; Rui Zhou (BioMetals, 2009)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)

Distribution and partition of polycyclic aromatic hydrocarbon in surface water of the Pearl River Estuary, South China - Xiao-Jun Luo; Bi-Xian Mai; Qing-Shu Yang; She-Jun Chen; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

The possible influence of stratospheric sudden warming on East Asian weather - Shumei Deng; Yuejuan Chen; Tao Luo; Yun Bi; Houfu Zhou (Advances in Atmospheric Sciences, 2008)

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Rice Allelopathy Induced by Methyl Jasmonate and Methyl Salicylate - Hai Hong Bi; Ren Sen Zeng; Li Ming Su; Min An; Shi Ming Luo (Journal of Chemical Ecology, 2007)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)